Assessment of Knowledge of Breast Cancer and Screening Methods among Nurses in University Hospitals in Addis Ababa, Ethiopia, 2011. (6th August 2013) - Lemlem, Semarya Berhe; Sinishaw, Worknish; Hailu, Mignote; Abebe, Mesfin; Aregay, Alemseged
Abstract : Background . According to the American Cancer Society, about 1.3 million women will be diagnosed with breast cancer annually worldwide and about 465, 000 will die from the disease. In Ethiopia breast cancer is the second most often occurring cancer among women. Early diagnosis is especially important for breast cancer because the disease responds best to treatment before it has spread. Objective . To assess knowledge of breast cancer and screening methods among nurses in university hospitals. Method . This cross-sectional descriptive study used simple random sampling on sample of 281 nurses. Structured questionnaires draw out responses about knowledge and screening method of nurses in regard to breast cancer. Bivariate analysis was used principally and variables were then entered to multiple logistic regressions model for controlling the possible effect of confounders and the variables which have significant association were identified on the basis of OR, with 95% CI and P value. Results . The findings of this study revealed that only 156 (57.8%) of them were knowledgeable about breast cancer and its screening and 114 (42.2%) were not. Knowledge of breast cancer was found to be significantly associated with regular course in nursing, family history of respondents, and unit of work. Conclusion and Recommendation . The results of this study indicate that the knowledge of nurses is not satisfying and highlight the need to improve the content in the nursing curriculum and to undergo more workplace training in the area of breast cancer and screening methods.